Aircraft stories : decentering the object in technoscience - Law, John, 1946- (Science and cultural theory., 2002)
A case study of a large military aircraft (TSR 2 from British Aircraft Corporation) which explores modernism and postmodernism and how we might think past the limits that these set to our ways of thinking.